SULTHAN AND IQRA’-ISTIQRA’ IN THE INTERNATIONALIZATION SPIRIT OF MUHAMMADIYAH EDUCATION - Khaidir, Piet Hizbullah (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2018)
This paper discloses the urgency of the concepts of sulthan and iqra?-istiqra? in the revitalization and realization of Muhammadiyah education. This effort is in line with the notions proposed by KH. Ahmad Dahlan, namely: (i) comprehension of tawhid; (ii) modernization of Islamic teachings and traditions; (iii) revitalization of Islamic values and teachings; (iv) repetition of Islamic teachings and tradition; and (v) realization of Islamic teachings into enlightening legacy. The challenge faced by current education is: how to encourage and generate students with creativity and self-esteem as well as multiple intelligences and skills. Based on the Qur?an [55: 33], being creative and dignified is the self-preparation to possess sulthan, namely: (i) knowledge (conceptual and technical); (ii) leadership management; (iii) interpersonal communication skills. Furthermore, the Qur?an [13: 11] also reveals this self-preparation requires a change of mindset (??), as an effort to have a perfect sulthan in terms of character or mentality. The Qur?an [96: 1-5] reveals those who have sulthan are continuously performed iqra? (deductive reasoning) and istiqra? (inductive reasoning). It is accompanied by devotion to the truth and respect for the dignity of human. Such a mentality can be developed through knowledge and discipline integrity, being open-minded and humble, and self-control. It is discussed in this paper by using philosophical approach and Qur'anic studies, particularly on the relation between the verses and KH. Ahmad Dahlan?s notions in the context of Muhammadiyah education.